Barriers and enablers to embedding fundamental nursing care for older patients—Implications of a mixed methods study for nursing leadership. (14th March 2022) - Grealish, Laurie; Ranse, Kristen; Todd, Jo‐Anne; Armit, Lyn; Billett, Stephen; Collier, Leigh; Bail, Kasia; Moyle, Wendy
Abstract: Aims: To understand the enablers and barriers for delivering fundamental care to hospitalized older patients. Design: Explanatory sequential mixed methods design, with qualitative data used to elaborate quantitative results. Methods: Set in one medical and one surgical unit of a tertiary hospital in southeast Queensland, Australia. Observations of nursing practice using the Work Sampling Technique were conducted over two 2‐week periods in 2019. Data were analyzed and presented to groups of nurses who appraised the findings of the observations. Results: There were 1176 and 1278 observations of care in the medical unit over two time periods and 1380 and 1398 observations over the same period in the surgical unit. Fundamental care activities were recorded in approximately 26% (i.e. medical) and 22% (i.e. surgical) of all observations. Indirect care was highest, recorded in 41% (i.e. medical) and 43% (i.e. surgical) of observations. Nurses prioritized the completion of reportable activities, which is perceived as a potential enabler of fundamental care. Potential barriers to fundamental care included frequent delays in indirect care and difficulty balancing care requirements across a group of patients when patients have high fundamental care needs. Conclusion: The cultural acceptance of missed nursing care has the potential to erode public confidence in health systems, where assistance with fundamental care is expected. Relational styles of nurse leadership should focus on: (1) making fundamental care important work in the nurses' scope thereby offering an opportunity for organizational change, (2) promoting education, demonstrating the serious implications of missed fundamental care for older patients and (3) investigating work interruptions. Impact: Fundamental care is necessary to arrest the risk of functional decline and associated hospital‐acquired complications in older patients. However, nurses commonly report fundamental care as missed or omitted care. Understanding the challenges of implementing fundamental care can assist in the development of nurse leadership strategies to improve older patients' care. Fundamental care was observed between 22% (i.e. surgical) and 26% (i.e. medical) of all observations. Nurses explained that they were focused on prioritizing and completing reported activities, experienced frequent delays when delivering indirect care and found balancing care requirements across groups of patients more challenging when patients had fundamental care needs. Clinical nurses working in acute health services with increasing populations of older patients can lead improvements to fundamental care provision through relational leadership styles to demonstrate how this work is in nurses' scope of practice, promote education about the serious implications of missed fundamental care and investigate the root cause of work interruptions.